Instrumentation development to study candidate materials for an organic piezoelectronic transistor - Afanasjevs, Sergejs (The University of Edinburgh, 2021)
High pressure (HP) is a powerful tool which is used to modify the material’s physical properties. The work described in this thesis is dedicated to the development of new or adaptation of the existing HP instrumentation which is capable of producing in situ conductivity (γ) measurements on the test materials to identify the most promising candidates for the organic piezoelectronic transistor (OPET). OPET is a concept of a new transistor which overcomes limitations of the currently employed transistor technology because it utilizes piezoelectric transduction rather than the electric field to propagate digital logic signals. This, in turn, implies small driving voltages, higher processing speeds and denser integration/scaling capabilities. The OPET device concept utilizes a piezoelectric actuator which, when the voltage (V) is applied to it, expands and, as a result, uniaxially compresses the thin layer of piezoresistive (PR) material within the rigid system. The employed PR materials need to have high pressure-dependent resistivity (ρ) to turn from the insulator/semiconductor into the conductor and, therefore, to pass the electric signal further within the ambient and 3 gigapascals (GPa) (pressure within the suitable range for OPET application). Among a wide variety of materials, organics were selected as PRs due to the high interest which they attracted in the recent decades by the worldwide multidisciplinary research in the electronic materials and because molecular organics are much more compressible than inorganic lattices. Although the OPET device concept implies the uniaxial compression, on the initial project stages it is rationally and economically viable to first characterise the PRs in the single crystal or the compressed powder form before their deposition into thin films. The characterisation implies the variable pressure (P) and variable temperature (T) ρ studies which resulted in necessity in developing double-layer autofrettaged piston-cylinder cell (PCC). The PCC is capable of reaching 3 GPa and is equipped with the feedthrough plug which introduces the probe wires into the HP environment to monitor sample resistance (R) and P changes in situ. To achieve P beyond the 3 GPa the DAC of the Merrill Bassett type was adapted for the electric γ measurements. DAC is equipped with 0.8 mm in diameter diamond culets and the NiCrAl seats to allow safe exploitation up to the 10 GPa to characterise those PR materials which failed to metallise within the desired P range but still are having a good ρ - P tendency which might find an application in the future OPET devices when better performance piezoelectric actuators will be made. Designs of both: PCC and DAC were analytically verified and validated using finite element analysis (FEA) as well as experimentally tested to indeed survive the P extremes with no yielding in the employed materials. Both cells were made to fit the required sample geometry with the necessary optimal probe contact separation which is the important prerequisite for the precise R into ρ conversion. In the case of the DAC the special sample loading techniques, gasket (a mechanical seal and a sample chamber between two opposed diamonds) preparation and insulation, as well as the gold sputtering of the probe contacts procedures, were implemented to achieve experimental success. Another HP cell which is reported in this thesis is the uniaxial high-pressure cell (UHPC). It was designed to produce both: static and dynamic P experiments to mimic the OPET device concept to study those PR materials which were deposited into the thin films. The performance of the above-mentioned P cells within this project is illustrated in the form of the project related outcomes. Among selected for the study materials, the hydrostatic HP measurements were performed on the platinum and iridium complexes with organic ligands, Magnus salts (organic-inorganic hybrids) as well as on the gold dithiolene complexes. The achieved results showed that some candidate materials indeed are promising for an application in the OPET device due to high P dependence on the electronic properties within the above-mentioned P range. For instance, the gold radical with (4-(4-chlorophenyl)-1,3-dithiolene) ligand and the Pt(bqd)2 materials were found to undergo 3 and 7 orders of magnitude change in ρ respectively between ambient pressure (Pamb) and 2 GPa at room T. The latter material was also deposited into the thin film form and exposed to the uniaxial HP. The produced measurements showed that the sample R gradually decreases from 600000 Ohm (Ω) at Pamb to 35 Ω at 0.11 GPa and values stay consistent between P cycles.
Keywords: high-pressure; HP instrumentation; organic piezoelectronic transistor; OPET; uniaxial high-pressure cell; UHPC